BRAND TRUST AND SERVICE QUALITY TO INCREASE CONSUMER SATISFACTION OF CIREBON BATIK (International Journal of Innovative Technologies in Economy, 2024)
Batik MSMEs are thriving despite challenges like changing fashion trends and global market shifts. Their unwavering focus on product quality sets them apart. Through continuous improvement of production methods and careful selection of raw materials, they produce exceptional batik that distinguishes itself in the market. This study aims to examine the effect of product brand trust and service quality on customer satisfaction. Conducted in Ciayumajakuning, the research involved 230 respondents from batik MSMEs. Using a sample size of 230, the study employed 23 indicators, with each observation representing 10 respondents. Quantitative methods were used, with incidental sampling as the technique. Data analysis was done using Structural Equation Modeling- Partial Least Square (SEM-PLS). The findings revealed a direct correlation between customer brand trust and purchase satisfaction, as well as service quality and customer satisfaction. The perceived customer value plays a crucial role in mediating the impact of brand trust and service quality on customer satisfaction.